UHF RFID antenna architectures and applications - Uddin, Md. Jasim; Reaz, Mamun Bin Ibne; Mohamed Hasan, Ahmed Abbas; Nordin, Anis Nurashikin; Ibrahimy, Muhammad Ibn; Ali, Mohd Alauddin Mohd (Academic Journals, 2010)
In order to use radio frequency identification (RFID) antenna for wireless communication and real world applications (e.g.) military and personal communication systems, mobile phones, personal digital assistant (PDA), blue-tooth systems, wireless local area networks (WLAN), railway vehicle identification, road tolling systems, fish tracking systems etc, studying the nature and characteristics of the antenna is an important use. The collective electrical signals acquired from RFID antennas require advanced techniques for feeding, gains and radiation patterns. The purpose of this paper is to review and discuss various algorithms and methodologies aimed at providing more flexible and efficient ways of analyzing RFID antenna. This paper further focused on the review of future implementation methodologies and performance comparison along with their applications. Some of the applications are illustrated at the end of the paper and recommended for further study is also outlined. This review serves as a comparative studies and reference beneficial for RFID antenna researchers, for future implementation of the technology. This review paper opens a corridor for researcher to perform future comparative studies between different architecture and model as a reference point for developing more powerful, flexible and efficient applications.